High-temperature-resistant melt-processable polyetherimide and preparation method thereof

The polyetherimide resin containing sulfide structure was prepared by solution polycondensation method, which solved the problem of softening of thermoplastic resin under high temperature conditions, achieved a balance between high glass transition temperature and good melt processability, and was suitable for the aerospace field.

CN119241840AActive Publication Date: 2025-01-03SICHUAN UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411578505.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-03
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

Existing thermoplastic resins are prone to soften under high temperature conditions, resulting in low glass transition temperature, affecting product performance and bringing safety hazards, and it is difficult to balance heat resistance and melt processability.

Method used

Polyetherimide resin containing sulfide structure is prepared by solution polycondensation method, and the oxidation time and temperature are controlled under the action of an oxidant to promote the oxidation of the polymer chain structure. Finally, high glass transition temperature and good washing are obtained by solvent phase separation and washing Melt-processable resin.

Benefits of technology

Polyetherimide resins with high glass transition temperature, good melt processability and mechanical strength have good thermal properties and structural controllability, and are suitable for harsh aerospace applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241840A_ABST
    Figure CN119241840A_ABST
Patent Text Reader

Abstract

The invention relates to high-temperature-resistant melt-processable polyetherimide and a preparation method thereof, and belongs to the technical field of polymer synthesis. The invention provides high-temperature-resistant melt-processable polyetherimide. The structural formula of the high-temperature-resistant melt-processable polyetherimide is shown as a formula I; n in the formula I is equal to 5-200, 0lt; and x is 1. According to the preparation method, thioether-containing diamine and commercial dianhydride are taken as raw materials, and high-molecular-weight polyetherimide with oxidation potential is prepared in one step; and then carrying out in-situ oxidation to prepare the thioether oxidized heat-resistant enhanced melt-processable polyetherimide. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-temperature resistant melt-processable polyetherimide and a preparation method thereof, belonging to the technical field of polymer synthesis. Background Art

[0002] With the rapid development of science and technology in human society, the demand for advanced polymer resins has become increasingly strong. Existing polymer resins can be roughly divided into thermoplastic resins and thermosetting resins. Thermoplastic resins with high heat resistance are widely used in the aerospace field because of their good melt processability and recyclability. However, the demand for heat resistance of polymer materials under extreme conditions has brought new challenges. Most of the existing thermoplastic resins, especially amorphous resins, have the problem of low glass transition temperature, and are prone to softening under high-temperature service conditions, which seriously affects the performance of the product and brings safety hazards. Therefore, the design and preparation of resins with high glass transition temperature and high heat resistance is of great practical significance.

[0003] For linear polymer materials, the higher the glass transition temperature of the resin, the higher the rigidity of the structural unit and the stronger the intermolecular force. Excessive structural rigidity and polarity will make the material difficult to process by thermoplasticity, and lose its application potential as a structural material in the aerospace field. Therefore, how to balance the heat resistance and melt processability of thermoplastic resins is a very important issue. The amorphous thermoplastic resin with the highest heat resistance grade on the market is polyethersulfone resin, including polyethersulfone (PES), polysulfone (PSF) and polyphenylene sulfone (PPSU). The glass transition temperature can reach 220°C, and it can be formed by common thermoplastic resin processing equipment such as extrusion and injection molding. From a chemical structure point of view, this type of resin contains both rigid and polar groups, such as benzene rings and sulfone groups; it also contains flexible and easy-to-process structures, such as oxygen ether and aliphatic methyl. It is precisely because of its rigid and flexible chemical structure that polyethersulfone achieves a balance between heat resistance and thermoplasticity at a high level.

[0004] However, the existing resin systems have not fully explored the heat resistance potential of thermoplastic resins, and lack a universal method to dynamically regulate the thermoplasticity and processability of resins. Zhuang Yongbing (Progress in Polymer Science, 2019, 35-88) and others from the University of the Chinese Academy of Sciences explored the glass transition temperature and processability of a series of polyetherimides containing flexible aliphatic structures and rigid imide structures. Chinese patents CN200510021105.6 and CN101538366B introduced flexible thioether structures into polyimides, explored the relationship between resin structure and performance, and proved that the polyetherimide structure has good thermal properties and structural controllability. Summary of the invention

[0005] The purpose of the present invention is to provide a polyetherimide with high temperature resistance and melt processability and a preparation method thereof in view of the insufficient high temperature resistance of existing thermoplastic resins, so as to serve the increasingly stringent demand for heat-resistant thermoplastic resins. The present invention first prepares a high molecular weight polyetherimide containing a sulfide structure by a solution polycondensation method; then, under the action of an oxidant, the oxidation time and temperature are controlled to promote the oxidation or partial oxidation of the polymer chain structure; finally, through solvent phase separation, washing is performed to obtain a pure polyetherimide resin. This method has the advantages of low cost, simple operation, and dynamic control of resin properties. The obtained resin has the advantages of high glass transition temperature, good melt processability and high mechanical strength.

[0006] The technical solution of the present invention:

[0007] The first technical problem to be solved by the present invention is to provide a high temperature resistant and melt-processable polyetherimide, the structural formula of which is shown in Formula I:

[0008]

[0009] In formula I, n=5-200, 0 <x≤1;

[0010]

[0011] At least one of;

[0012]

[0013] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned high temperature resistant and melt-processable polyetherimide, the preparation method comprising: oxidizing the polyetherimide resin containing a sulfide structure shown in formula II;

[0014]

[0015] Where n = 5 to 200, 0 <x≤1;

[0016]

[0017] At least one of;

[0018]

[0019] Furthermore, the preparation method of the above-mentioned high-temperature resistant and melt-processable polyetherimide is: stirring the polyetherimide resin containing a sulfide structure shown in formula II, a non-protonic solvent and an oxidant at 10 to 80° C. for 1 to 72 hours; then precipitating the crude resin by non-solvent phase separation; and then filtering, washing and drying to obtain the high-temperature resistant and melt-processable polyetherimide.

[0020] Furthermore, in the above preparation method, the aprotic solvent is any one of m-cresol, o-dichlorobenzene, N-methylpyrrolidone, N,N-dimethylformamide, N,N-diethylacetamide, N,N-dimethyl sulfoxide or sulfolane. The addition amount of the aprotic solvent is determined by the mass of the polyetherimide resin, and the mass ratio of the aprotic solvent to the polyetherimide resin is 6:4 to 9:1.

[0021] Furthermore, in the above preparation method, the oxidant is at least one of hydrogen peroxide, concentrated sulfuric acid, nitric acid, formic acid, acetic acid, peracetic acid, ammonium persulfate aqueous solution or sodium hypochlorite aqueous solution.

[0022] Furthermore, in the above preparation method, the mass of the actual oxidation component of the oxidant accounts for 1-25 wt% of the mass of the polyetherimide resin containing a thioether structure shown in Formula II. An excessive content of the oxidant will cause phase separation of the polyetherimide in the solvent system, reducing the contact probability between the oxidant and the molecular chain, and it is difficult to prepare a polymer with a high glass transition temperature; an insufficient content of the oxidant will result in insufficient oxidation of the thioether, and it is also difficult to prepare a polymer with a high glass transition temperature.

[0023] Furthermore, in the above preparation method, the oxidation temperature of the stirring reaction is 10-80 °C; an excessive oxidation temperature will cause rapid decomposition of the oxidant, making it difficult to effectively promote the oxidation process of the thioether for a long time; an insufficient oxidation temperature is difficult to overcome the energy barrier for the oxidation of the thioether to a sulfone group, and it is also difficult to promote the oxidation process of the thioether.

[0024] Furthermore, in the above preparation method, the solvent for the non-solvent phase separation means is any one of water, ethanol, methanol or petroleum ether.

[0025] Furthermore, in the above preparation method, it is dried until the water content ≤ 0.1 wt%.

[0026] The third technical problem to be solved by the present invention is to provide a polyetherimide resin containing a thioether structure, and its structural formula is as shown in Formula II:

[0027]

[0028] where n = 5-200, 0 < x ≤ 1; preferably, 0.2 < x ≤ 1;

[0029]

[0030] at least one of;

[0031]

[0032] The fourth technical problem to be solved by the present invention is to provide a method for preparing the polyetherimide resin containing a sulfide structure, wherein the method comprises: reacting dianhydride and diamine monomers in an aprotic solvent and nitrogen or inert gas atmosphere at 120 to 220° C. for 3 to 36 hours to obtain the polyetherimide resin containing a sulfide structure; wherein the dianhydride is bisphenol A diether dianhydride (BPADA);

[0033] The diamine is selected from one of the following combinations:

[0034] 1) The diamine is 4,4'-diaminodiphenyl sulfide;

[0035] 2) The diamine is substance A and substance B, wherein substance A is any one of 4,4'-diaminodiphenyl sulfide, 4,4'-(1,4-phenylene disulfide) diphenylamine, 4,4'-((thiobis(1,4-phenylene))disulfide) diphenylamine, 4,4'-((sulfonylbis(1,4-phenylene))disulfide) diphenylamine, 4,4'-((ketobis(1,4-phenylene))disulfide) diphenylamine, 4,4'-([1,1'-biphenyl]-4,4'-diylbis(sulfide)) diphenylamine, thien-2,7-diamine, dibenzo[b,d]thiophene-2,7-diamine or 4,4'-(thien-2,7-diyldisulfide) diphenylamine; and substance B is 4,4'-diaminodiphenyl oxide.

[0036] Furthermore, in the method for preparing the polyetherimide resin containing a sulfide structure, the molar ratio of the dianhydride to the diamine is 0.95:1 to 1:1.05, and more preferably, the molar ratio is 1:1.

[0037] Furthermore, in the preparation method of the polyetherimide resin containing a thioether structure, when the diamine is selected as combination 2), the molar ratio of substance A to substance B is 1:4 to 7:3. Considering the potential for regulating the heat resistance and processability of the subsequent oxidized polymer, the copolymerization ratio x of the aromatic amine containing a thioether bonded structure should be greater than 0%, and the copolymerization ratio x should be greater than 20% and less than or equal to 70%.

[0038] Furthermore, in the preparation method of the polyetherimide resin containing a sulfide structure, the aprotic solvent is any one of m-cresol, o-dichlorobenzene, N-methylpyrrolidone, N,N-dimethylformamide, N,N-diethylacetamide, N,N-dimethyl sulfoxide or cyclopentane. The amount of the aprotic solvent added is determined by the sum of the feed amounts of the dianhydride monomer and the diamine monomer, and the mass ratio of the aprotic solvent to the dianhydride and diamine monomers is 6:4 to 9:1.

[0039] Furthermore, in the preparation method of the polyetherimide resin containing a sulfide structure, the reaction temperature is 150-200° C. and the reaction time is 6-15 hours; the reaction monomer and the solvent are added into the reaction container at one time, and then the temperature is raised to a predetermined temperature at one time for reaction.

[0040] Furthermore, in the method for preparing the polyetherimide resin containing a sulfide structure, the atmosphere is at least one of nitrogen, argon and helium.

[0041] Beneficial effects of the present invention:

[0042] 1. The present invention uses thioether-containing diamine and commercial dianhydride as raw materials to prepare high molecular weight polyetherimide with oxidation potential in one step; then in-situ oxidation is performed to prepare thioether-oxidized heat-resistant reinforced polyetherimide that can be melt-processed. The process is simple, there is no need to wash the intermediate product, and there are few by-products.

[0043] 2. The present invention adopts a reasonable copolymerization ratio to obtain a polyetherimide resin having both high heat resistance and melt processability.

[0044] 3. The present invention adopts low-cost oxidants and can safely and efficiently regulate the thermal properties and processability of polyetherimide by controlling temperature and time. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is the infrared spectrum (FT-IR spectrum) of the oxidized polyetherimide obtained in Example 2. DETAILED DESCRIPTION

[0046] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents used or the unspecified manufacturers are all conventional products that can be purchased commercially.

[0047] Example 1

[0048] 468.4g of bisphenol A type diether dianhydride, 97.2g of 4,4'-diaminodiphenyl sulfide, 90.0g of 4,4'-diaminodiphenyl oxide, and 2200mL of o-dichlorobenzene were added to a glass reactor. Under nitrogen protection, the temperature was raised to 180°C within 1 hour and the reaction was continued for 10 hours. It was observed that the viscosity of the system gradually increased. After the polymerization reaction was completed, the reaction was cooled to room temperature to obtain a polyetherimide resin containing a sulfide structure.

[0049] Next, add 150mL of 30% mass fraction hydrogen peroxide and 50mL of formic acid into the polymer solvent system, stir thoroughly and react at 60°C for 24h; cool and discharge, pour the polymer system into 8000mL of methanol solution for precipitation; filter the obtained crude resin product, wash it three times with hot methanol solution and water solution, dry it to a water content of ≤0.1%, and finally obtain the oxidized polyetherimide resin (high temperature resistant melt-processable polyetherimide). Verify that all are book strengths in this step

[0050] Example 2

[0051] 468.4g of bisphenol A diether dianhydride, 194.4g of 4,4'-diaminodiphenyl sulfide, and 2200mL of o-dichlorobenzene were added to a glass reactor. Under nitrogen protection, the temperature was raised to 180°C within 1 hour. After reacting for 10 hours, it was observed that the viscosity of the system gradually increased. After the polymerization reaction was completed, the reaction was cooled to room temperature to obtain a polyetherimide resin containing a sulfide structure.

[0052] Next, add 150 mL of 30% mass fraction hydrogen peroxide and 50 mL of formic acid into the polymer solvent system, stir thoroughly at 60°C and react for 24 hours; cool and discharge, pour the polymer system into 8000 mL of methanol solution for precipitation. The crude resin product obtained by filtration is washed three times with hot methanol solution and aqueous solution, dried to a water content of ≤0.1%, and finally the oxidized polyetherimide resin is obtained. The performance parameters of the embodiment are shown in Table 1. The infrared spectrum of the prepared oxidized polyetherimide is shown in Figure 1 shown.

[0053] Example 3

[0054] 468.4g of bisphenol A diether dianhydride, 194.4g of 4,4'-diaminodiphenyl sulfide, and 2200mL of o-dichlorobenzene were added to a glass reactor. Under nitrogen protection, the temperature was raised to 180°C within 1 hour. After reacting for 10 hours, it was observed that the viscosity of the system gradually increased. After the polymerization reaction was completed, the reaction was cooled to room temperature to obtain a polyetherimide resin containing a sulfide structure.

[0055] Next, 150 mL of 30% mass fraction hydrogen peroxide and 50 mL of formic acid were added to the polymer solvent system, fully stirred and reacted at 60°C for 6 hours; the material was cooled and discharged, and the polymer system was poured into 8000 mL of methanol solution for precipitation. The crude resin product obtained by filtration was washed three times with hot methanol solution and aqueous solution, dried to a water content of ≤0.1%, and finally the oxidized polyetherimide resin was obtained. The performance parameters of the comparative example are shown in Table 1.

[0056] Example 4

[0057] 468.4g of bisphenol A diether dianhydride, 194.4g of 4,4'-diaminodiphenyl sulfide, and 2200mL of o-dichlorobenzene were added to a glass reactor. Under nitrogen protection, the temperature was raised to 180°C within 1 hour. After reacting for 10 hours, it was observed that the viscosity of the system gradually increased. After the polymerization reaction was completed, the reaction was cooled to room temperature to obtain a polyetherimide resin containing a sulfide structure.

[0058] Next, 150 mL of 30% mass fraction hydrogen peroxide and 50 mL of formic acid were added to the polymer solvent system, fully stirred and reacted at 60°C for 12 hours; the material was cooled and discharged, and the polymer system was poured into 8000 mL of methanol solution for precipitation. The crude resin product obtained by filtration was washed three times with hot methanol solution and aqueous solution, dried to a water content of ≤0.1%, and finally the oxidized polyetherimide resin was obtained. The performance parameters of the comparative example are shown in Table 1.

[0059] Example 5

[0060] 468.4g of bisphenol A diether dianhydride, 194.4g of 4,4'-diaminodiphenyl sulfide, and 2200mL of o-dichlorobenzene were added to a glass reactor. Under nitrogen protection, the temperature was raised to 180°C within 1 hour. After reacting for 10 hours, it was observed that the viscosity of the system gradually increased. After the polymerization reaction was completed, the reaction was cooled to room temperature to obtain a polyetherimide resin containing a sulfide structure.

[0061] Next, 150 mL of 30% mass fraction hydrogen peroxide and 50 mL of formic acid were added to the polymer solvent system, fully stirred and reacted at 25°C for 24 hours; the material was cooled and discharged, and the polymer system was poured into 8000 mL of methanol solution for precipitation. The crude resin product obtained by filtration was washed three times with hot methanol solution and aqueous solution, dried to a water content of ≤0.1%, and finally the oxidized polyetherimide resin was obtained. The performance parameters of the comparative example are shown in Table 1.

[0062] Example 6

[0063] 468.4g of bisphenol A type diether dianhydride, 97.2g of 4,4'-(1,4-phenylene disulfide) diphenylamine, 120.2g of 4,4'-diaminodiphenyl oxide, and 2200mL of o-dichlorobenzene were added to a glass reactor. Under nitrogen protection, the temperature was raised to 180°C within 1 hour and the reaction was continued for 10 hours. It was observed that the viscosity of the system gradually increased. After the polymerization reaction was completed, the reaction was cooled to room temperature to obtain a polyetherimide resin containing a sulfide structure.

[0064] Next, 150 mL of 30% mass fraction hydrogen peroxide and 50 mL of formic acid were added to the polymer solvent system, fully stirred and reacted at 60°C for 24 hours; the material was cooled and discharged, and the polymer system was poured into 8000 mL of methanol solution for precipitation. The crude resin product obtained by filtration was washed three times with hot methanol solution and aqueous solution, and dried to a water content of ≤0.1%, and finally the oxidized polyetherimide resin was obtained. The performance parameters of the embodiment are shown in Table 1.

[0065] Example 7

[0066] 468.4g of bisphenol A type diether dianhydride, 194.4g of 4,4'-(1,4-phenylene disulfide) diphenylamine, 60.1g of 4,4'-diaminodiphenyl oxide, and 2200mL of o-dichlorobenzene were added to a glass reactor. Under nitrogen protection, the temperature was raised to 180°C within 1 hour and the reaction was continued for 10 hours. It was observed that the viscosity of the system gradually increased. After the polymerization reaction was completed, the reaction was cooled to room temperature to obtain a polyetherimide resin containing a sulfide structure.

[0067] Next, 150 mL of 30% mass fraction hydrogen peroxide and 50 mL of formic acid were added to the polymer solvent system, fully stirred and reacted at 60°C for 24 hours; the material was cooled and discharged, and the polymer system was poured into 8000 mL of methanol solution for precipitation. The crude resin product obtained by filtration was washed three times with hot methanol solution and aqueous solution, and dried to a water content of ≤0.1%, and finally the oxidized polyetherimide resin was obtained. The performance parameters of the embodiment are shown in Table 1.

[0068] Example 8

[0069] 468.4g of bisphenol A type diether dianhydride, 120.2g of 4,4'-([1,1'-biphenyl]-4,4'-diylbis(sulfadiyl))diphenylamine, 120.2g of 4,4'-diaminodiphenyl oxide, and 2200mL of o-dichlorobenzene were added to a glass reactor. Under nitrogen protection, the temperature was raised to 180°C within 1 hour and the reaction was continued for 10 hours. It was observed that the viscosity of the system gradually increased. After the polymerization reaction was completed, the reaction was cooled to room temperature to obtain a polyetherimide resin containing a sulfide structure.

[0070] Next, 150 mL of 30% mass fraction hydrogen peroxide and 50 mL of formic acid were added to the polymer solvent system, fully stirred and reacted at 60°C for 24 hours; the material was cooled and discharged, and the polymer system was poured into 8000 mL of methanol solution for precipitation. The crude resin product obtained by filtration was washed three times with hot methanol solution and aqueous solution, and dried to a water content of ≤0.1%, and finally the oxidized polyetherimide resin was obtained. The performance parameters of the embodiment are shown in Table 1.

[0071] Example 9

[0072] 468.4g of bisphenol A type diether dianhydride, 180.2g of 4,4'-([1,1'-biphenyl]-4,4'-diylbis(sulfadiyl))diphenylamine, 90.1g of 4,4'-diaminodiphenyl oxide, and 2200mL of o-dichlorobenzene were added to a glass reactor. Under nitrogen protection, the temperature was raised to 180°C within 1 hour and the reaction was continued for 10 hours. It was observed that the viscosity of the system gradually increased. After the polymerization reaction was completed, the reaction was cooled to room temperature to obtain a polyetherimide resin containing a sulfide structure.

[0073] Next, 150 mL of 30% mass fraction hydrogen peroxide and 50 mL of formic acid were added to the polymer solvent system, fully stirred and reacted at 60°C for 24 hours; the material was cooled and discharged, and the polymer system was poured into 8000 mL of methanol solution for precipitation. The crude resin product obtained by filtration was washed three times with hot methanol solution and aqueous solution, and dried to a water content of ≤0.1%, and finally the oxidized polyetherimide resin was obtained. The performance parameters of the embodiment are shown in Table 1.

[0074] Comparative Example 1

[0075] 468.4g of bisphenol A diether dianhydride, 259.2g of 4,4'-(1,4-phenylene disulfide) diphenylamine, 20.0g of 4,4'-diaminodiphenyl oxide, and 2200mL of o-dichlorobenzene were added to a glass reactor. Under nitrogen protection, the temperature was raised to 180°C within 1 hour. The reaction was continued for 10 hours, and the viscosity of the system was observed to gradually increase. After the polymerization reaction was completed, the reaction was cooled to room temperature.

[0076] Next, 150 mL of 30% mass fraction hydrogen peroxide and 50 mL of formic acid were added to the polymer solvent system, fully stirred and reacted at 60°C for 24 hours; the material was cooled and discharged, and the polymer system was poured into 8000 mL of methanol solution for precipitation. The crude resin product obtained by filtration was washed three times with hot methanol solution and aqueous solution, dried to a water content of ≤0.1%, and finally an oxidized polyetherimide resin was obtained; the performance parameters of the obtained oxidized polyetherimide resin are shown in Table 1.

[0077] Comparative Example 2

[0078] 468.4g of bisphenol A type diether dianhydride, 270.3g of 4,4'-([1,1'-biphenyl]-4,4'-diylbis(sulfadiyl))diphenylamine, 45.1g of 4,4'-diaminodiphenyl oxide, and 2200mL of o-dichlorobenzene were added to a glass reactor. Under nitrogen protection, the temperature was raised to 180°C within 1 hour. The reaction was continued for 10 hours, and the viscosity of the system was observed to gradually increase. After the polymerization reaction was completed, the reaction was cooled to room temperature.

[0079] Next, 150 mL of 30% mass fraction hydrogen peroxide and 50 mL of formic acid were added to the polymer solvent system, fully stirred and reacted at 60°C for 24 hours; the material was cooled and discharged, and the polymer system was poured into 8000 mL of methanol solution for precipitation. The crude resin product obtained by filtration was washed three times with hot methanol solution and aqueous solution, dried to a water content of ≤0.1%, and finally an oxidized polyetherimide resin was obtained; the performance parameters of the obtained oxidized polyetherimide resin are shown in Table 1.

[0080] Table 1 Performance parameters of polyetherimide obtained in Examples 1-4 and Comparative Examples 1-2

[0081] Glass transition temperature(℃) <![CDATA[Weight-average molecular weight (mol·g -1 )]]> Melt Processability Example 1 232 35270 good Example 2 258 33480 good Example 3 221 32170 good Example 4 243 32450 good Example 5 216 31540 good Example 6 236 37520 good Example 7 253 39230 generally Example 8 243 35260 good Example 9 262 36780 generally Comparative Example 1 325 34190 Difference Comparative Example 2 287 32890 Difference

[0082] a. Glass transition temperature test: nitrogen atmosphere, heating rate 10℃ / min.

[0083] b. Weight average molecular weight test: use N,N-dimethylformamide as the mobile phase.

[0084] c. Melt processability evaluation criteria: extruder screw speed is 120rpm, homogenization section temperature is 350℃, observe whether the resin can plasticize the tie rod evenly (good: the resin can plasticize the tie rod evenly; average: the resin can plasticize, but the color will become darker, shark skin and other phenomena will appear; poor: the resin is difficult to completely plasticize, and the melt viscosity is too high).

Claims

1. A high temperature resistant melt processable polyetherimide, characterized in that: Its structural formula is shown in Formula I: In formula I, n=5-200, 0 <x≤1; R3= At least one of; R4= 2. The method for preparing a high temperature resistant melt-processable polyetherimide according to claim 1, characterized in that: The preparation method comprises: oxidizing a polyetherimide resin having a thioether structure as shown in formula II; Where n = 5 to 200, 0 <x≤1; R1= At least one of; R2= 3. The method for preparing a high temperature resistant melt-processable polyetherimide according to claim 2, characterized in that: The preparation method of the high-temperature resistant and melt-processable polyetherimide is as follows: a polyetherimide resin containing a thioether structure shown in formula II, a non-protonic solvent and an oxidant are stirred and reacted at 10 to 80° C. for 1 to 72 hours; a crude resin is precipitated by a non-solvent; and the crude resin is filtered, washed and dried to obtain the high-temperature resistant and melt-processable polyetherimide.

4. The method for preparing a high temperature resistant melt-processable polyetherimide according to claim 3, characterized in that: The aprotic solvent is any one of m-cresol, o-dichlorobenzene, N-methylpyrrolidone, N,N-dimethylformamide, N,N-diethylacetamide, N,N-dimethyl sulfoxide or sulfolane.

5. The method for preparing a high temperature resistant melt-processable polyetherimide according to any one of claims 2 to 4, characterized in that: The oxidant is at least one of hydrogen peroxide, concentrated sulfuric acid, nitric acid, formic acid, acetic acid, peracetic acid, ammonium persulfate aqueous solution or sodium hypochlorite aqueous solution; Furthermore, the mass of the actual oxidizing component of the oxidant accounts for 1 to 25 wt % of the mass of the polyetherimide resin containing a sulfide structure represented by Formula II.

6. The method for preparing a high temperature resistant melt-processable polyetherimide according to any one of claims 2 to 5, characterized in that: The oxidation temperature of the stirring reaction is 10-80°C.

7. A polyetherimide resin containing a thioether structure, characterized in that: Its structural formula is shown in Formula II: Where n = 5 to 200, 0 <x≤1; R1= At least one of; R2= 8. The polyetherimide resin containing a thioether structure according to claim 7, characterized in that: The preparation method comprises: reacting dianhydride and diamine monomers in an aprotic solvent and nitrogen or inert gas atmosphere at 120 to 220° C. for 3 to 36 hours to obtain the polyetherimide resin containing a sulfide structure; wherein the dianhydride is bisphenol A type diether dianhydride; The diamine is selected from one of the following combinations: 1) The diamine is 4,4'-diaminodiphenyl sulfide; 2) The diamine is substance A and substance B, wherein substance A is any one of 4,4'-diaminodiphenyl sulfide, 4,4'-(1,4-phenylene disulfide) diphenylamine, 4,4'-((thiobis(1,4-phenylene))disulfide) diphenylamine, 4,4'-((sulfonylbis(1,4-phenylene))disulfide) diphenylamine, 4,4'-((ketobis(1,4-phenylene))disulfide) diphenylamine, 4,4'-([1,1'-biphenyl]-4,4'-diylbis(sulfide)) diphenylamine, thien-2,7-diamine, dibenzo[b,d]thiophene-2,7-diamine or 4,4'-(thien-2,7-diyldisulfide) diphenylamine; and substance B is 4,4'-diaminodiphenyl oxide.

9. The polyetherimide resin containing a thioether structure according to claim 8, characterized in that: The molar ratio of the dianhydride to the diamine is 0.95:1 to 1:1.05; or: The aprotic solvent is any one of m-cresol, o-dichlorobenzene, N-methylpyrrolidone, N,N-dimethylformamide, N,N-diethylacetamide, N,N-dimethyl sulfoxide or sulfolane; or: The reaction temperature is 150-200° C. and the reaction time is 6-15 hours; or: The reaction monomers and the solvent are added into the reaction container at one time, and then the temperature is raised to a predetermined temperature at one time to react.

10. The polyetherimide resin containing a thioether structure according to claim 9, characterized in that: When the diamine is selected as combination 2), the molar ratio of substance A to substance B is 1:4 to 7:3.

Citation Information

Patent Citations

  • Polyetheriminde film and multilayer structure

    CN101128513A

  • Moisture resistant polyimide compositions

    CN102245678A

  • Preparation method of thermosetting polyimide

    CN109942816A

  • Diamine compound containing sulfoxide-based bridge chain as well as synthesis method and application of diamine compound containing sulfoxide-based bridge chain

    CN111763162A

  • One-step method for preparing polyimide by taking organic aromatic acid as reaction medium

    CN113912848A